Simultaneous RP-HPLC Estimation of Salbutamol, Ambroxol and Theophylline in Tablets - Sivasubramanian, Lakshmi (Asian Journal of Chemistry, 2010)
A simple, fast, precise and accurate liquid chromatographic method was developed for the simultaneous estimation of salbutamol, ambroxol and theophylline in tablets. This combination is used for the treatment of bronchial asthma. Drugs are chromatographed on a reverse phase Hypersil C18 column using mobile phase, phosphate buffer (pH 7.0), methanol and acetonitrile in the ratio 40:30:30 (v/v). The retention time of salbutamol, ambroxol and theophylline was 3.07, 4.91 and 1.77 min, respectively. The validation of the proposed method was also carried out. The method was found to be linear (correlation coefficient r > 0.999), precise (relative standard deviation: 0.42 % for salbutamol, 0.61 % for ambroxol and 0.73 % for theophylline), accurate (overall average recovery yields: 99 % for salbutamol, 101.2 % for ambroxol and 99.8 % for theophylline) and selective. Due to its simplicity and accuracy, the proposed method can be used for routine quality control analysis of these drugs in combination tablets.